Renal Denervation in Asia: Consensus Statement of the Asia Renal Denervation Consortium. Issue 3 (March 2020) - Kario, Kazuomi; Kim, Byeong-Keuk; Aoki, Jiro; Wong, Anthony Yiu-tung; Lee, Ying-Hsiang; Wongpraparut, Nattawut; Nguyen, Quang Ngoc; Ahmad, Wan Azman Wan; Lim, Soo Teik; Ong, Tiong Kiam; Wang, Tzung-Dau
Abstract : The Asia Renal Denervation Consortium consensus conference of Asian physicians actively performing renal denervation (RDN) was recently convened to share up-to-date information and regional perspectives, with the goal of consensus on RDN in Asia. First- and second-generation trials of RDN have demonstrated the efficacy and safety of this treatment modality for lowering blood pressure in patients with resistant hypertension. Considering the ethnic differences of the hypertension profile and demographics of cardiovascular disease demonstrated in the SYMPLICITY HTN (Renal Denervation in Patients With Uncontrolled Hypertension)-Japan study and Global SYMPLICITY registry data from Korea and Taiwan, RDN might be an effective hypertension management strategy in Asia. Patient preference for device-based therapy should be considered as part of a shared patient-physician decision process. A practical population for RDN treatment could consist of Asian patients with uncontrolled essential hypertension, including resistant hypertension. Opportunities to refine the procedure, expand the therapy to other sympathetically mediated diseases, and explore the specific effects on nocturnal and morning hypertension offer a promising future for RDN. Based on available evidence, RDN should not be considered a therapy of last resort but as an initial therapy option that may be applied alone or as a complementary therapy to antihypertensive medication.